The role of outer membrane protein(S) harboring slh/oprb-domains in extracellular vesicles’ production in synechocystis sp. pcc 6803 - Cardoso, D (2021)
Cyanobacteria are a group of photosynthetic prokaryotes that contribute to primary production on a global scale. These microorganisms release vesicles to the extracellular environment, spherical nanosized structures, derived essentially from the outer membrane. Even though earlier works in model Gram-negative bacteria have hypothesized that outer membrane stability is crucial in vesicle formation, the mechanisms determining vesicle biogenesis in cyanobacteria remain unknown. Here, we report on the identification of six candidate genes encoding outer membrane proteins harboring SLH/OprB-domains in the genome of the model cyanobacterium Synechocystis sp. PCC 6803. Using a genetics-based approach, one gene was found to encode an essential protein (Slr1841), while the remaining five are not essential for growth under standard conditions. Vesicle production was monitored, and it was found that a mutant in the gene encoding the second most abundant SLH/OprB protein in Synechocystis sp. PCC 6803 outer membrane (Slr1908) produces more vesicles than any of the other tested strains. Moreover, the Slr1908-protein was also found to be important for iron uptake. Altogether, our results suggest that proteins containing the SLH/OprB-domains may have dual biological role, related to micronutrient uptake and to outer membrane stability, which, together or alone, seem to be involved in cyanobacterial vesicle biogenesis.